2010
DOI: 10.3354/meps08793
|View full text |Cite
|
Sign up to set email alerts
|

Variability in connectivity indicated by chaotic genetic patchiness within and among populations of a marine fish

Abstract: Despite substantial advances in our understanding of marine population dynamics, there is still much uncertainty as to what processes influence connectivity, gene flow and population structure. To explore this, we examined the spatial and temporal variation in population genetic structure of adult and recently settled bicolor damselfish Stegastes partitus, a coral reef fish. We genotyped adult and juvenile fish from 10 sites over 4 sample years at 9 microsatellite loci. We show spatial heterogeneity in adult a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 68 publications
(108 reference statements)
8
85
2
Order By: Relevance
“…Genomic DNA was extracted from samples using a platebased extraction method (Elphinstone et al 2003), and genotyping was performed as follows (full details are described in Hogan et al 2010). In brief, nine microsatellite loci were chosen from the literature (Williams et al 2003;Thiessen and Heath 2007) and screened for suitability.…”
Section: Genotypingmentioning
confidence: 99%
See 4 more Smart Citations
“…Genomic DNA was extracted from samples using a platebased extraction method (Elphinstone et al 2003), and genotyping was performed as follows (full details are described in Hogan et al 2010). In brief, nine microsatellite loci were chosen from the literature (Williams et al 2003;Thiessen and Heath 2007) and screened for suitability.…”
Section: Genotypingmentioning
confidence: 99%
“…At smaller spatial scales, Ospina-Guerrero et al (2008) found genetic homogeneity among sites within the Columbian Caribbean (*400 km), suggesting high levels of gene flow at this scale. However, three studies found weak (Hepburn et al 2009;Hogan et al 2010) to strong (Villegas-Sanchez et al 2010) genetic structuring at a similar scale in the MBRS, showing evidence of more restricted or variable gene flow. Christie et al (2010) found direct evidence of larval retention (i.e., self-recruitment) in Bahamian populations of S. partitus, on a backdrop of high gene flow among sites (*250 km).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations